Selection of the fermentation conditions for the growth of Bacillus subtilis BSVN15 used in production of probiotic for livestock - Hương, Phương Thị; Hạnh, Vũ Văn (Vietnam Journal of Biotechnology, 2018)
Some strains of Bacillus subtilis are widely used in the probiotic production for various areas, especilly utilized in feed production.B. subtilis group that have the ability to produce internal spores. They are very resistant to acid pH in animal stomach. .B. subtilis group that produce various enzymesregarding digestion of food and inhibit pathogens. Thus, which contribute to reducing the use of antibiotics. In this study, the growth conditions of Bacillus subtilis BSVN15 strain was selected to apply for probiotic production for feeds. For convenience, the biomass results were presented as CFU/ml (colony forming units per ml) of Bacillus subtilis BSVN15 strain from various fermentation liquid culture conditions. The study was conducted in LB* (Luria-Bertani)* broth medium (in the LB medium peptone was replaced by tryptone). Various selected parameters including fermentation time (hrs), inoculumn size (%, v/v), temperature of fermentation, pH value of culture, various carbon sources and various concentrations of carbon, some nitrogen sources and some nitrogen concentrations, some supplemental metal ion sources. Selected fermentation conditions included pH 7 of liquid culture, 37oC of incubation, 7% (v/v) of inoculation size, glucose concentration of 1.5% (w/v) as the main carbon source, peptone conccentration of 1% (w/v), Ca2+of 50 mM, 24 hours of culture time, as a biomass of Bacillus subtilis BSVN15 strain reached 6.3 x 1011 CFU/mL. In the best selected fermentation condition, the biomass (CFU / mL) was produced about 26 times higher than that of normal fermentation at the same temperature of 30oC, shaking incubator 200 rpm, in basical Luria-Bertani broth.